The Impact of Training Programs on Improving Employee Efficiency and Productivity: A Case Study of King Salman Medical City n Medina - Al-Muhaimidi , Abdullah Mastour; Al-Suhaimi , Yasser Ali; Al-Suhaimi , Nayef Ghabeisan; Al-Rashidi , Satam Muflih; Al-Jahani , Fahd Al-Afi; Al-Suhaimi , Salwa Ali; Al-Suhaimi , Atallah Awadh; Al-Suhaimi , Fahd Hamid; Al-Suhaimi , Salah Ghabeisan; Shaker , Issam Mohamed (Journal of Ecohumanism, 2024)
The study aimed to identify the level of training programs in the medical units of King Salman Bin Abdulaziz Medical City and to measure the level of efficiency and productivity of employees in the medical units of King Salman Bin Abdulaziz Medical City. It also aimed to highlight the importance of using training programs with employees in King Salman bin Abdulaziz Medical City. The study adopted the descriptive methodology, relying on a questionnaire for data collection. The questionnaire was distributed to a stratified random sample of 100 employees in the three hospitals of King Salman Medical City in Medina. The SPSS statistical analysis program was used to analyze the data. The study found a statistically significant relationship between training programs and the improvement of employee efficiency and productivity in the three hospitals of King Salman Medical City in Medina. Additionally, there was a statistically significant relationship between the number of training courses attended at King Salman Medical City and the efficiency and productivity of employees.